2019
DOI: 10.1186/s41077-019-0114-9
|View full text |Cite
|
Sign up to set email alerts
|

Failure affects subjective estimates of cognitive load through a negative carry-over effect in virtual reality simulation of hip fracture surgery

Abstract: BackgroundCognitive overload can impair learning, and different factors might affect cognitive load during simulation-based training. In this study, we investigate the role of failure in repeated practice of virtual reality (VR) simulation of hip fracture surgery on cognitive load (CL) estimated by secondary-task reaction time test and two questionnaires.MethodsThe VR simulation training program consisted of three competency levels of increasing complexity starting with the placement of a Kirschner wire in a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Respondents were prompted to “reflect on a day [they] performed clinical work during the last 1-2 weeks that is representative of a typical current clinical work day” and rate their perception of each subscale demand type on a scale of 0 to 100 (with 100 being the highest level of demand) [ 38 , 39 ]. The 4 scores were summed for a composite score ranging from 0 to 400 [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were prompted to “reflect on a day [they] performed clinical work during the last 1-2 weeks that is representative of a typical current clinical work day” and rate their perception of each subscale demand type on a scale of 0 to 100 (with 100 being the highest level of demand) [ 38 , 39 ]. The 4 scores were summed for a composite score ranging from 0 to 400 [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…From a medical education point of view, future studies are needed to investigate whether a summative LC-CUSUM test promotes or hinders formative acquisition of technical competencies. The latter might be the case, because the LC-CUSUM test punishes failed simulations harshly, causing frustration (Rölfing et al 2019 ). Thus, it is relevant to investigate if LC-CUSUM should be included or if other more motivating learning strategies should be applied in simulation-based training programs.…”
Section: Discussionmentioning
confidence: 99%
“…The second theme discusses learning curves and changes in performance using these simulations. A total of 14 papers [26][27][28][29][30][31][32][33][34][35][36][37][38][39] investigated this theme (Table 2). The third theme reports on reviews of orthopaedic VR simulators and evidence of their usefulness in orthopaedic training.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Conversely, Camp et al 28 found that residents who trained on cadaveric specimens improved twice as fast as those who had VR-based training, for diagnostic knee arthroscopies. Rolfing et al 35 noted participant frustration to be a barrier for simulation training programmes. Nevertheless, a cost analysis showed VR simulation to be more cost-effective if utilized properly.…”
Section: Learning Curves and Subject Performancementioning
confidence: 99%